Estudio Etnobotánico de la Chuquiragua en las parroquias de Chugchilán, Isinliví y Zumbahua de la provincia de Cotopaxi - Sasintuña Vasquez, David Fernando (2021)
The traditions and cultural expressions associated with the use of the Chuquiragua in the communities of Chugchilán, Isinliví and Zumbahua, today are threatened due to the social processes that the planet is going through, one of them is globalization. In this regard, the identification of the cultural knowledge associated with the use of Chuquiragua, through an ethnobotanical study through the elaboration of a catalog of uses of the Chuquiragua, allows us to evaluate and structure actions to conserve the cultural heritage belonging to the social group " Panzaleo ”. Thus, the identification of the key actors in the communities belonging to the aforementioned parishes is of utmost importance, since they are the watchdogs and transmitters of cultural resources to future generations, allowing the maintenance of these expressions for posterity. The compilation of information to key actors through field evaluation instruments such as interviews and INPC files, help the researcher to have a broader and more precise notion of the subject, and based on the bibliographic review, allow the researcher to Identify and support the different uses, applications, knowledge, etc., that encompass the use of this Parameño shrub. Among the most relevant uses that are given to this shrub based on the results obtained, are the medicinal use and the ornamental use, the first use being the one that has the greatest reception among the inhabitants of these parishes, due to its curative properties. and its association with Andean cosmology. However, the main problem lies in the correct transmission of this knowledge to future generations, as part of a process of recovering their cultural identity. In this sense, capturing the ideas in a written document such as an ethnobotanical catalog referring to the Chuquiragua, allows us to demonstrate the results obtained in the field work and also helps us to reflect new perspectives with avant-garde themes that range from the Botanical descriptive area, such as: “Parts of the Chuquiragua”, “Taxonomy of the Chuquiragua”, “Distribution and conservation status of the Chuquiragua”, and “Key characteristics among species of the genus Chuquiraga”; to the cultural area where topics of interest are exposed such as: "The flower of the walker or of the mountaineer", "Relationship between the little star of Chimborazo and the Chuquiragua", "Medicinal properties of the Chuquiragua" and the "Legend of the Chuquiragua" . By providing a document that meets the most relevant characteristics regarding the cultural resources associated with the use of the Chuquiragua, a basis for future projects associated with this plant is generated, and therefore the generation of a state of conservation will be a key aspect for new research.